Area‐Based Geocoding: An Approach to Exposure Assessment Incorporating Positional Uncertainty. (24th November 2021) - Thompson, Laura K.; Langholz, Bryan; Goldberg, Daniel W.; Wilson, John P.; Ritz, Beate; Tayour, Carrie; Cockburn, Myles
Abstract: While the spatial resolution of exposure surfaces has greatly improved, our ability to locate people in space remains a limiting factor in accurate exposure assessment. In this case‐control study, two approaches to geocoding participant locations were used to study the impact of geocoding uncertainty on the estimation of ambient pesticide exposure and breast cancer risk among women living in California's Central Valley. Residential and occupational histories were collected and geocoded using a traditional point‐based method along with a novel area‐based method. The standard approach to geocoding uses centroid points to represent all geocoded locations, and is unable to adapt exposure areas based on geocode quality, except through the exclusion of low‐certainty locations. In contrast, area‐based geocoding retains the complete area to which an address matched (the same area from which the centroid is returned), and therefore maintains the appropriate level of precision when it comes to assessing exposure by geography. Incorporating the total potential exposure area for each geocoded location resulted in different exposure classifications and resulting odds ratio estimates than estimates derived from the centroids of those same areas (using a traditional point‐based geocoder). The direction and magnitude of these differences varied by pesticide, but in all cases odds ratios differed by at least 6% and up to 35%. These findings demonstrate the importance of geocoding in exposure estimation and suggest it is important to consider geocode certainty and quality throughout exposure assessment, rather than simply using the best available point geocodes. Plain Language Summary: Understanding the relationship between environmental exposures and cancer development is limited by how precisely we can locate people. While ideally all estimates would be based on building‐level precision, epidemiologic research must accommodate varying levels of locational accuracy, and is dependent on input address data quality (often patient addresses). This study uses traditional point‐based geocoding and a novel method of geocoding (area‐based) to estimate the relationship between ambient pesticide exposure and breast cancer. Although a "point" representing a geocoded location implies precision, point coordinates can be based on anything from an exact building centroid to an entire city and may miss relevant exposure for larger areas. Using area‐based geocoding, exposure estimation for an address resolved only to its ZIP Code is based on the entire ZIP Code area. We identified more individuals with potential pesticide exposure using area‐based geocoding. Importantly, the proportion of exposed cases and controls was inconsistent across geocoding methods and varied by pesticide, resulting in changes in the estimated exposure‐disease relationship. Geocoding quality plays a critical role in environmental exposure research, and misclassification may not be consistent or readily predictable. Methods incorporating spatial uncertainty (e.g., area‐based geocoding), may shed more light on this issue and support improvements. Key Points: Area‐based geocoding includes the precise area of uncertainty on an address‐by‐address basis, which is not possible using current methods Geocode positional error can bias exposure and associated risk estimates in unpredictable ways Area‐based geocoding incorporates heterogeneity of the exposure surface that likely plays a role in the magnitude and direction of biases